2021
DOI: 10.21608/ejchem.2021.67171.3450
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Ameliorative Effect of Bacillus subtilis against the Toxicity Induced by Aflatoxin B1 in Rats

Abstract: Aflatoxin B1 (AFB1) is the most toxic and common among the major types of aflatoxins. AFB1 is hepatoxic and has been implicated in an increase risk of hepatocellular carcinoma, also the effect of AFs on the brain chemistry have been documented. Probiotics have health benefits and provide of powerful benefits for the body and brain. The present study was designed to reveal efficiency of Bacillus subtilis NS4182-01 against the hematological, biochemical and histopathological alterations induced by AFB1 in rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 82 publications
1
2
0
Order By: Relevance
“…It is well known that CPF affected spleen and bone marrow cells by accelerating apoptosis and inducing the DNA damage [ 75 ]. The current study showed that indices of red blood cells (RBCs, HB, HCT, MCV, RDW, MPV, and PLT) declined in the CPF-intoxicated group and this was in agreement with Deabes et al [ 76 ] who demonstrated that the hematological measurements were altered in the CPF-injected group due to elevating products of the peroxidation reactions as a consequence of stimulating the oxidative stress. Moreover, the differential WBCs decreased in the CPF-injected group compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It is well known that CPF affected spleen and bone marrow cells by accelerating apoptosis and inducing the DNA damage [ 75 ]. The current study showed that indices of red blood cells (RBCs, HB, HCT, MCV, RDW, MPV, and PLT) declined in the CPF-intoxicated group and this was in agreement with Deabes et al [ 76 ] who demonstrated that the hematological measurements were altered in the CPF-injected group due to elevating products of the peroxidation reactions as a consequence of stimulating the oxidative stress. Moreover, the differential WBCs decreased in the CPF-injected group compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…This was coincided with Hashem and El-Sharkawy [ 77 ] who reported that CPF caused lymphopenic leucopenia due to the oxidative damage to the leukocytes. Treatment of the CPF-injected rats with Au- C. equisetifolia nano-extract normalized levels of these measurements in all groups treated with nano-extract, and this might be attributed to the existence of various polyphenolic compounds with high antioxidant activity and high ability to scavenge the ROS generated due to the exposure to CPF [ 76 ]. The nano-extract is rich in the active phytoconstituents which are able to improve absorption of iron by facilitating conversion of the iron from the ferrous (oxidized) state to the ferric (reduced) state in addition to ameliorating the integrity of the RBCs and WBCs compromised by the oxidative stress induced by CPF [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that B.Clausii can protect the structural integrity and prevent AFB1-induced kidney damage in mice. This matches most of the studies that studied the effect of probiotics on reducing the toxic effects in the body of a laboratory organism, including what it did (Deabes et al, 2021) The study was designed to reveal the efficiency of Bacillus subtilis NS4182-01 against the haematological, biochemical and histopathological alterations induced by AFB1 in rats. Both AFB1 and B.subtilis were studied on the experimental animals (rats) Groups 5&6 (AFB1 + B.subtilis group) were orally treated with AFB1 and then treated with B.subtilis at two studied doses respectively.…”
Section: Histopathological Observations To Clarify the Protective Eff...mentioning
confidence: 82%